Next generation intelligent converged metro network - Chang CAO; Shuai ZHANG; Xiongyan TANG (Dianxin kexue)
First of all,the main issues in current operator metro network were analyzed,the background of why intelligent metro network and the main technologies of the application were introduced.Then the network deployment plans and service organization plans according to the scale of the metro network and the timeline for introduction of all related technologies were introduced.At last,a stage-by-stage exposition regarding to the fusion mode of communication cloud and intelligent converged metro network during deployment process was presented.Based on a series of analysis,it was pointed out that the construction of intelligent metro network played a very important role in the process of SDN/NFV network reconfiguration and cloud network fusion.It’s of great value to bear existing metro network services synthetically and cope with future services on the collaboration of cloud,network and edge.It’s necessary to accumulate operation experiences continuously in the deployment process.